(untitled) (Journal of Nepalese Business Studies, 2018)
Entrepreneurship is perceived as an effective way to escape from poverty and paternalism. In developing countries, the informal sector is an important source of employment. Micro-enterprise is a tiny industry usually of 1-10 people that is profit-oriented and may be owned by a man or a woman. Micro Enterprise Development Programme (MEDEP) is launched in the country with technical and financial support of United Nations development Programme (UNDP) since 1998. Parbat and Baglung districts are selected for the purpose of fieldwork. Objectives of the study are to identify practices of business registration, nature and types of enterprises, location of business, conducted of main business and entrepreneurs manage their business premises. The study is based on survey research approach. Data are collected through primary sources. Both qualitative and quantitative data have been used in this study. The result shows that out of total respondents 78.6 percent respondents did not register their firm in concern authority. Main reasons for not registered their business in concerned authorities is as follows: respondents have no knowledge, lengthy procedures; registration office is too far, costly, difficult to fill in the forms, and other reasons for not being registered. The result of study shows that out of total micro enterprises, 83.9 percent enterprise belongs to sole proprietorship and 10.8 percent belongs to partnership. To identify nature of business, there were given seven options. It is found that out of total respondents, near about fifty percent entrepreneurs have agro-based enterprises, 15.8 percent and 15.2 percent entrepreneurs have forest –based enterprise, and skilled-based enterprises respectively. The result shows that most of the entrepreneurs conducted their business in rural area i.e. 90.6 percent. An attempt has been made to identify conducted main business through questionnaire and it is found that out of total entrepreneurs, more than two third entrepreneurs conducted their business in their own land and building. Another survey result showed that 80.6 percent entrepreneurs arrange their business premises in without rent. It seems that most of the entrepreneurs conduct their business in rent free premises. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page: 20-27